A 5-HT Antagonist (UP 26-91) versus Codeine and Placebo in a Human Experimental Pain Study - Lars Arendt-Nielsen; Poul Pedersen; Lars Poulsen; Ole Kæseler Andersen; Peter Bjerring; Isabelle Coste; Jorge Insuasty; Søren Sindrup; Asbjørn Mohr Drewes (Pain Research and Management)
BACKGROUND: This double-blind, randomized, crossover study compared the potential analgesic effect of the serotonin receptor antagonist UP 26-91 (50 mg, 150 mg and 300 mg) with that of codeine (100 mg) and placebo by use of different human experimental pain models.